CRITICAL ANALYSIS OF SAMANYA KARNAROGA NIDANA WSRT BADHIRYA - Dr.Sreeshma V, Dr.Ashutosh Kar; Dr. A B Biradar, (EPRA International Journal of Research and Development (IJRD), 2023)
Badhirya is one among the 28 karnarogas described in classics.Based on dosa we can classify it into 2 types like vata and vatakaphaja. Hearing loss is the impairment in hearingit can be partial or complete. Defect at any level from sound transduction to interpretation can cause hearing loss.Modern science classify hearing loss as three types conductive hearing loss, Sensory neural hearing loss and mixed hearing loss. Samanya Karna roganidanas include Avasyaya, Jalakrida,Karnakandu,Mithya yoga of sastra &sabda,Pratisyaya by different acharyas. Here is an attempt made to think how the Samanya Karna roganidanas are leading to Badhirya (hearing loss).